Implementasi Metode DSDM Pada SIPELAKOR - Dini Silvi Purnia; Devi Fauziah Nur (Indonesian Journal on Software Engineering (IJSE), 2018)
Abstract - Posyandu is a unit of the Ministry of Health implemented a working area in shade local health centers. The Ministry of health integrated program is usually done each month. In service there are a number of issues including Posyandu officer posyandu do record keeping and reporting in the form of a paper record-keeping or paperbase. This is a very slow process of work of the officers of the posyandu and not efisien Posyandu services process and often the parents who come to the Posyandu by not bringing KMS made the parents do not have a handle to monitor Toddler development so that in this study enulis information systems Design Services make Posyandu as Monitoring Developments for parents (SIPELAKOR) as one of the solutions of the problems of the existing system running at Posyandu to help simplify the entire process of service development and monitoring of Posyandu Toddlers using Dynamic System Development Method (DSDM) as a method of development lnak and the Unified Modelling Language (UML) as an Object-based visual modeling tools for designing this Posyandu services system. Keywords : Dynamic Systems Development Method (DSDM),Posyandu, information systems, and the Unified Modeling Language (UML)